Estimating Egypt's Equilibrium Real Exchange Rate - Mongardini, Joannes (IMF Working Papers; Working Paper ;, 1998)
In light of the real appreciation of the Egyptian pound over the last six years and Egypt's lackluster export growth, questions of external competitiveness and exchange rate policy have arisen. This paper sheds light on these issues by estimating empirically Egypt's equilibrium real exchange rate, that is, the rate that is consistent with fundamentals. The results show that, while the real exchange rate was substantially overvalued before 1993, today it is only moderately above the equilibrium rate. Moreover, the analysis shows that the recent appreciation of the pound does not indicate a worsening misalignment.